Effects of honours programme participation in higher education: a propensity score matching approach. Issue 6 (19th September 2017) - Kool, Ada; Mainhard, Tim; Jaarsma, Debbie; van Beukelen, Peter; Brekelmans, Mieke
ABSTRACT: Honours programmes have become part of higher education systems around the globe, and an increasing number of students are enrolled in such programmes. So far, effects of these programmes are largely under-researched. Two gaps in previous research on the effects of such programmes were addressed: (1) most studies lack a comparable control group of students not enrolled in honours programmes and (2) few studies have longitudinally investigated effects of honours programmes on student characteristics other than academic achievement. By using propensity score matching, the current study investigated the effects of Dutch honours programmes on students' ability, motivation, creativity and academic achievement. Students' self-perceived ability, perseverance, mastery orientation, performance orientation, intellectual curiosity and self-efficacy, as well as students' gender and study grades were used to match undergraduate honours students to non-honours students ( N = 94). Results showed no overall differences in ability, motivation and creativity halfway into the honours programme, although honours students seemed to slightly increase in intellectual curiosity, while non-honours students tended to decrease in mastery orientation. Outcomes of the study give rise to considerations about the role of honours programmes in curricula.